Table of Content - - (Journal of Curriculum and Teaching Methodology, 2025)
Table of Content: The extent to which Islamic studies teachers in Makkah Al-Mukarramah practice the dimension of digital respect in achieving intellectual security for secondary school female students from the teachers’ point of view Ms. Nidaa Adeel Alhashmi, Prof. Hubah Ahmad Akram The Effectiveness of Utilizing a Software Based on Spatial Intelligence Strategies in Developing Architectural Design Thinking Skills Among 11th-Grade Female Students Ms. Zouwaina Khalaf Al-Ghawi, Asst-Prof. Noor Ahmed Al-Najar The Extent of Inclusion the Concepts of Sustainable Development in Content of Islamic Studies for the for third level in intermediate school in Saudi Arabia Mr. Abdulwahab Abdullah Almalki, Asst-Prof. Mohammed Saad Alqarni Criteria for designing Smart Micro-learning Environments to develop Cognitive Mastery in the Biology Course for Secondary School Students in The Kingdom of Saudi Arabia Mr. Ali Ahmed Al-Nasheri, Prof. Ashraf Ahmed Zeidan ,Co-Prof. Bassim Rafi Al-Shehri The Reality of Expressive and Receptive Skills among Early Childhood Students from the Point of View of Teachers and supervisors and Ways to develop it Ms. Ashwaq Aloush Al-Dweish, Asst-Prof. Amna’ah Hejr A program that began developing the Nadham structural model using Arduino and its effectiveness in developing Python and task programming skills among high school students Dr. Amsha Munahi Alqahtani, Prof. Khaled Ibrahim Al-Turki Effectiveness of an Inclusive Education-Based Instructional Unit in Enhancing Students’ Knowledge of 3D Clothing Design Software Ms. Bdoor Abdullah Hazazi, Dr. Sahar Hassan Ejeimi